Pengaruh Digital Marketing Terhadap Minat Beli Konsumen Pada Market Place Shopee Di Kecamatan Tidore - Ruray, Titiek Arafiani (Peneliti.net, 2025)
This study aims to examine the effect of digital marketing on consumer buying interest at the shopee market place in Tidore District. Digital marketing is a marketing strategy that is that is carried out onlien using various digital media platforms, such as websites,social media,e-mail,and market places. One of the popular market places.one of the popular market places in Indonesia is Shoppe. The study uses a quantitative approach, by collecting data from respondents who are active shoppe users in Tidore Ditrict. The sample used in this study amounted to 40 respondents and used a non-probability sampling technique. The data analysic used was correlation analysis and simple linear regression analysis using SPSS version 20 software.The results of the data analysis showed that there was a positive influence between digital marketing and consumer purchasing power of 3.45%.